Evaluation of the Rocks of The Pila Spi Formation of Duhok Anticline For Building Stones – Kurdistan Region Of Iraq - Khalid, Ameer H. (Science Journal of University of Zakho, 2021)
The rocks of the Pila Spi Formation at the southern limb of the Duhok anticline have been evaluated for use as building stones. The geology of the area and examined rocks are described. Nine samples were collected and tested for physico-mechanical properties (total porosity, water absorption, saturation coefficient, apparent specific gravity, bulk density and uniaxial compressive strength). There was a remarkable variation between the samples in these properties, which showed very high significant relationships with each other. Samples were classified as frost-resistant. According to the Iraqi and American Standards, four samples were categorized as (low density/acceptable), three samples as (moderate density/recommended) and two samples as (high density/highly recommended). According to some classifications, the samples were (moderately strong) except for two of them were (strong), while all of them were (moderately strong) and (high strength rocks) in other classifications. The examined rocks are suitable for interior and exterior wall cladding and exterior fencing, as well as for decoration. Four of them are not suitable for building sections that require high load bearing or in places where they come into contact with water or soil, such as foundations, while only two samples are suitable. The quality and quantity of the rocks and the quarrying conditions encourage their exploitation for building stones, with the necessity of proper planning of the proposed quarry and special treatment during quarrying.
Keywords: Building Stones; Duhok Anticline; Kurdistan Region; Physico-mechanical Properties; Pila Spi Formation; Quarrying